PTSD Symptoms After Traumatic Versus Stressful Life Events in People With Mild Intellectual Disabilities: Proving the Null - Rouleaux, Mariëlle; Peters‐Scheffer, Nienke; Bouwmeester, Samantha; Lindauer, Ramón; Mevissen, Liesbeth; Didden, Robert (Journal of intellectual disability research, 2025)
ABSTRACT Background Research in people without ID suggests that both traumatic events (i.e., A criterion events) and stressful life events (i.e., non‐A criterion events) can produce PTSD symptoms. However, research on this subject in ID populations is limited. The discussion about the usefulness of Criterion A (i.e., the stressor criterion) as a gate criterion for PTSD in the DSM‐5‐TR is particularly important for people with mild intellectual disabilities (MID) or borderline intellectual functioning (BIF) because of their vulnerability to stressors. This study aimed to compare PTSD symptoms and impairment of daily life functioning (IDLF) score following traumatic versus stressful index events in people with MID‐BIF. Methods The Diagnostic Interview Trauma and Stressors–Intellectual Disability (DITS‐ID) was administered to 54 participants with MID‐BIF. Two groups were generated based on the type of index event (i.e., traumatic or stressful). Bayesian equivalence testing was used to assess whether the two groups differed in terms of PTSD symptoms and IDLF score. Results Data were more consistent with either a small difference or no difference at all between the traumatic (N = 22) and stressful group (N = 32) regarding the mean number of PTSD symptoms and the mean IDLF score. Differences in PTSD symptoms and IDLF scores ranged from 0.00 to 0.87. Conclusion No clinically relevant differences were found between the traumatic and stressful groups in terms of mean number of PTSD symptoms and IDLF score. Stressful life events might produce PTSD symptoms in people with MID‐BIF.